The Influence of Organizational Culture, Work Environment and Work Stress on Employee Performance in the SMT Department of PT Aohai Technology Indonesian - Simanjuntak, Nova Yanti; Yanti, Sri (Universitas Batam, 2022)
This study aims to obtain empirical evidence of the influence of organizational culture, work environment, and job stress on employee performance at PT Aohai Technology Indonesia. In the testing phase in this research, the sampling method used is the census. The sample in this study were 110 employees of PT Aohai Technology Indonesia. The method of data collection is done by questionnaire. Hypothesis testing is done by using a linear regression model and T- statistical test. Hypothesis testing is done using SPSS software. Based on the results of testing the first hypothesis, it is known that organizational culture does not significant effect on the performance of employees of PT Aohai Technology Indonesia. And from the results of the second test, it is known that the work environment has a significant effect on the performance of employees of PT Aohai Technology Indonesia. And the results of the third test, it is known that work stress has a significant negative effect on the performance of PT Aohai Technology Indonesia.